2021
DOI: 10.3389/fcell.2021.719491
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Analysis Reveals Greater Epithelial Ridge Cells Degeneration During Postnatal Development of Cochlea in Rats

Abstract: Greater epithelial ridge cells, a transient neonatal cell group in the cochlear duct, which plays a crucial role in the functional maturation of hair cell, structural development of tectorial membrane, and refinement of audio localization before hearing. Greater epithelial ridge cells are methodologically homogeneous, while whether different cell subtypes are existence in this intriguing region and the degeneration mechanism during postnatal cochlear development are poorly understood. In the present study, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Greater epithelial ridge cells, also referred to as Kölliker’s organ (KO) ( Dou et al, 2021 ) are temporary structures during the development of cochlear hearing, during which there is programmed apoptosis and autophagy, and they eventually degenerate and disappear after the cochlear hearing has matured ( Hou et al, 2019 , 2020 ). From the dynamic change analysis of cell numbers, four-cell clusters, 0, 3, 4, and 6, showed a gradual decrease in cell numbers from P1 to P14 and disappeared on P14, and we tentatively considered four cell clusters 0, 3, 4, and 6 as different subtypes of GER cells ( Chen et al, 2021 ), which is consistent with Kolla’s study ( Kolla et al, 2020 ). In addition, we also found that clusters 2, 7, 9, and 12 showed an increase in the number of cells from P1 to P7, while degenerated and disappeared at P14 days ( Figure 2 and Supplementary Table 1 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Greater epithelial ridge cells, also referred to as Kölliker’s organ (KO) ( Dou et al, 2021 ) are temporary structures during the development of cochlear hearing, during which there is programmed apoptosis and autophagy, and they eventually degenerate and disappear after the cochlear hearing has matured ( Hou et al, 2019 , 2020 ). From the dynamic change analysis of cell numbers, four-cell clusters, 0, 3, 4, and 6, showed a gradual decrease in cell numbers from P1 to P14 and disappeared on P14, and we tentatively considered four cell clusters 0, 3, 4, and 6 as different subtypes of GER cells ( Chen et al, 2021 ), which is consistent with Kolla’s study ( Kolla et al, 2020 ). In addition, we also found that clusters 2, 7, 9, and 12 showed an increase in the number of cells from P1 to P7, while degenerated and disappeared at P14 days ( Figure 2 and Supplementary Table 1 ).…”
Section: Resultssupporting
confidence: 89%
“…Considering that the cochlear auditory development of P7 rats is not fully mature, it is still in a process of orderly differentiation and gradual developmental maturation ( Tritsch et al, 2007 ; Tritsch and Bergles, 2010 ). Based on our previous study ( Chen et al, 2021 ), we further selected the P14 time point jointly with the three key periods of P1, P7 for a single-cell transcriptomic study, and we found that the four previously identified subtypes of GER cell populations 0, 3, 4, and 6 gradually decreased from P1 to P14, and disappeared by P14 days ( Figure 1B ). However, it is interesting and noteworthy that we found four cell clusters (clusters 2, 7, 9, and 12) with similar spatial distribution and gene expression ( Figures 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that Hedgehog signaling inhibits the sensory differentiation ability of Kölliker's organ-supporting cells, regulates the fate of Kölliker's organ-supporting cells, and induces cochlear developmental maturation (Driver et al, 2008). Chen et al (2021b) performed KEGG signaling pathway analysis in different subtypes of Kölliker's organ-supporting cells by scRNA-seq and found that genes in different subtypes of Kölliker's organ-supporting cells were significantly enriched in the Ribosome signaling pathway; however, in the Cluster 3, a large number of genes were enriched in the Ribosome signaling pathway and Protein digestion and absorption signaling pathway. The Ribosome signaling pathway is an important signaling pathway that regulates cell proliferation and development (Pelletier et al, 2018).…”
Section: Molecular Signaling Pathways Of Kölliker's Organ-supporting ...mentioning
confidence: 99%
“…GER and LER can be distinguished by the molecular marker neural cadherin (N‐cad) (for GER) and epithelial cadherin (E‐cad) (for LER) (Simonneau et al, 2003). GER plays a crucial role in the functional maturation of hair cells, structural development of tectorial membrane, and refinement of the auditory system before hearing (Chen, Gao, et al, 2021; Lim, 1987). Part of the tectorial membrane is also produced by LER and substructures of the tectorial membrane are formed with the help of several different GLSs (Lim, 1987).…”
Section: Introductionmentioning
confidence: 99%